A cooperação internacional brasileira na educação superior: uma análise comparativa entre a Universidade Federal da Integração Latino-Americana – UNILA e a Universidade da Integração Internacional da Lusofonia Afro-Brasileira – UNILAB - Fernández, Daniela Tamaraz (2017)
Considering that the Federal University for Latin American Integration - UNILA and the University for International Integration of the Afro-Brazilian Lusophony - UNILAB are higher educational institutions in Brazil, created during the government of the then President Luiz Inácio Lula da Silva (2003-2010) , which seeks to promote international integration with the countries of Latin America and the CPLP (The Community of Portuguese Language Countries), especially in Africa, the objective is to analyze the process of creating UNILA and UNILAB, based on the proposal of Brazilian international cooperation in the area of Higher Education and the rapprochement with the countries of Global South within South-South Cooperation. To do so, a comparative analysis is carried out between the two universities, based on the foundational documents of UNILA and UNILAB, as well as an analysis of the experiences of social actors who participated in different stages of the creation process and establishing of both educational projects, through thematic interviews using oral history as a methodological approach. Thus, it is observed that the guidelines of the Brazilian Foreign Policy and the proposal of international cooperation in this period prioritized the dialogue with the Latin American and African countries, which became strategic partners in the context of the Brazilian rise as an emerging power in the international scene.